Serum folate levels among healthy infants aged 6-8 months: relation to infants' nutritional status indicators and maternal knowledge-attitude-practice (Medical Journal of Indonesia, 2011)
Background: Vitamin B12 and folate deficiency can cause anemia which may lead growth and development impairments. This study was aimed to determine serum folate levels among infants aged 6-8 months and the relation to infants' nutritional indicators and maternal knowledge-attitude-practice about infant feeding. Methods: A cross-sectional design was implemented in infants aged 6-8 months and their mothers as respondents who met the study criteria. Data collected among the infants included sex, age, length, weight, intake of energy, protein and folate (based on a one-month semi-quantitative FFQ and a 24-hour food recall), serum folate and hemoglobin levels. Data collected among the mothers included age, education level, income based on average minimum monthly wage, knowledge, attitude and behavior concerning infant's feeding, i.e. breast milk and complementary feeding practices. Results: This study found that the median of serum folate levels was 43.05 nmol/L with values ranging from 19.92 nmol/L to 104.24 nmol/L. Serum folate level had a strong positive correlation with its related factors, protein and folate intake. Conclusions: Protein-folate-rich complementay food should be provided to infants aged 6 months and over to maintain serum folate level. (Med J Indones 2011; 20:138-42)